2010
DOI: 10.5021/ad.2010.22.4.444
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Epidermal Cysts in Lowe Syndrome

Abstract: Fig. 1. Direct sequencing of OCRL1 gene of this patient disclosed a splice site mutation in exon 14 (IVS13-1G>A), and his mother was a heterozygous carrier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 8 publications
(17 reference statements)
0
15
0
Order By: Relevance
“…These resemble eruptive vellus hair cysts [76] but may also originate from mature hair follicles [77]. Won et al reported large epidermal cysts located on the scalp [78]. The etiology of these findings is unclear but has been related to increased extracellular concentrations of lysosomal enzymes [76].…”
Section: Clinical Manifestations and Managementmentioning
confidence: 99%
“…These resemble eruptive vellus hair cysts [76] but may also originate from mature hair follicles [77]. Won et al reported large epidermal cysts located on the scalp [78]. The etiology of these findings is unclear but has been related to increased extracellular concentrations of lysosomal enzymes [76].…”
Section: Clinical Manifestations and Managementmentioning
confidence: 99%
“…A further case presented with multiple eruption cysts in the oral cavity and hematoma formation [98]. Won et al [134] found various skin lesions reported to be skin colored, deep seated, with soft cystic masses on the temporal and occipital scalp. The histological examination showed each cyst to be lined by true epidermis composed of several layers of stratified squamous epithelium and a granular layer containing keratinous materials arranged in laminated layers.…”
Section: Dermatological Findingsmentioning
confidence: 99%
“… 7 There were several case reports of solitary giant EC on the gluteal region 8 , 9 , 13 and several cases of multiple ECs on the scalp. 10 , 11 However, there was just one case report of multiple EC on several locations. 10 In this case report, the patient had a rare clinical manifestation of EC.…”
Section: Discussionmentioning
confidence: 99%
“…3 There are several case reports of giant EC on the gluteal region 8 , 9 and several case reports of multiple ECs on hairy scalp. 10 , 11 However, there was only one case report of multiple ECs which spread to several locations of the body. 12 In this report, we present a case of generalized multiple ECs with a giant EC on the left gluteal region which is an unusual and rare manifestation of EC.…”
Section: Introductionmentioning
confidence: 99%